The Dynamics of Promise in DSN-MUI Fatwa Number 106/DSN-MUI/X/2016 Regarding the Endowment of Insurance Benefits and Investment Benefits in Sharia Life Insurance - Eva Fauziah; Panji Adam Putra; Cecep Soleh Kurniawan (Law Development Journal, 2026)
The differing opinions among Islamic jurists regarding the legal standing of a promise (wa’d) have led to at least three distinct scholarly views on the matter. In the context of implementing Islamic financial products in Indonesia, the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) has legitimized waqf of insurance benefits through Fatwa DSN-MUI No. 106/DSN-MUI/X/2016 concerning Waqf of Insurance Benefits and Investment Benefits in Islamic Life Insurance. The legal framework of this fatwa is based on the binding nature of a promise in law, as stated in the fatwa’s provisions. According to the fatwa, the designated party receiving insurance benefits is required to make a legally binding promise (wa’d mulzim) to dedicate the insurance benefits as waqf. The legal standing of a binding promise is further supported by Fatwa DSN-MUI No. 85/XII/2012 on promises in Islamic financial and business transactions. DSN-MUI holds that a binding promise (wa’d mulzim) aligns with the third juristic opinion, which asserts that fulfilling a promise is obligatory when the promise is conditional or contingent upon a specific cause. This view is deemed more beneficial (maslahah) and meets the necessary requirements (hajah), particularly in the context of waqf of insurance and Islamic investment benefits. In issuing its fatwas, especially Fatwa DSN-MUI No. 85/XII/2012, the DSN-MUI employs two approaches to legal solutions (makhârij fiqhiyyah): the method of al-taysir al-manhaji (methodological facilitation) and i’âdah al-nadzhar (re-evaluation).